Nucleotide analogues with immunobiological properties: 9-[2-Hydroxy-3-(phosphonomethoxy)propyl]-adenine (HPMPA), -2,6-diaminopurine (HPMPDAP), and their N6-substituted derivatives - Potmesil, Petr; Krecmerová, Marcela; Kmonícková, Eva; Holý, Antonín; Zídek, Zdenek (European journal of pharmacology, 2006)
Newly developed acyclic nucleoside phosphonates, derivatives of adenine and 2,6-diaminopurine bearing the 2-hydroxy-3-(phosphonomethoxy)propyl (HPMP) moiety at the N9-side chain (i.e., HPMPA and HPMPDAP, respectively) were screened for in vitro immunobiological activity, using mouse resident peritoneal macrophages and splenocytes. Both HPMPA and HPMPDAP augmented the interferon-gamma-triggered production of NO as well as expression of inducible nitric oxide synthase (iNOS) mRNA in macrophages. HPMPDAP activated secretion of tumor necrosis factor-alpha (TNF-alpha), chemokines "regulated-upon-activation, normal T cell expressed and secreted" (RANTES) and macrophage inflammatory protein-1alpha (MIP-1alpha), and marginally also secretion of interleukin-10 (IL-10) in both macrophages and splenocytes. The HPMPA, less prominently than HPMPDAP, elevated only secretion of RANTES and TNF-alpha. The compounds also activated secretion of TNF-alpha (HPMPDAP > HPMPA) in human peripheral blood mononuclear cells (PBMC). Distinct N6-substituted derivatives, i.e., N6-dimethyl-, N6-cyclopropyl-, N6-piperidin-1-yl-, N6-(2-methoxyethyl)-, N6-(2-hydroxyethyl)-, N6-allyl- and N6-2-(dimethylamino)ethyl-HPMPA/HPMPDAP as well as 6-thio and 6-hydroxy derivatives usually showed loss of the activity compared to the parent compounds. The immunomodulatory effects were found to be at least in part dependent on P1 purinoreceptors, and mediated by transcriptional factor nuclear factor-kappaB.
Keywords: Animals; synthasa oxidu dusnatého, typ II; vztah mezi dávkou a účinkem léčiva; Female; Cytokines; lipopolysacharidy; Adenine; Interferon-gamma; nukleotidy; Organophosphorus Compounds; ženské pohlaví; Receptors, Purinergic P1; triazoly; Caffeine; Molecular Structure; cytokiny; Quinazolines; Mice; purinergní receptory P1; messenger RNA; Dihydropyridines; organofosforové sloučeniny; polymerázová řetězová reakce s reverzní transkripcí; Lipopolysaccharides; myši; interferon gama; RNA, Messenger; molekulární struktura; Nucleotides; kofein; Purinergic P1 Receptor Antagonists; organofosfonáty; Dose-Response Relationship, Drug; Triazoles; adenin; Reverse Transcriptase Polymerase Chain Reaction; chinazoliny; dihydropyridiny; Nitric Oxide Synthase Type II; peritoneální makrofágy; exprese genu; oxid dusnatý; Cell Survival; zvířata; viabilita buněk; antagonisté purinergního receptoru P1; Mice, Inbred C57BL; Organophosphonates; Nitric Oxide; Gene Expression; Macrophages, Peritoneal; myši inbrední C57BL